2019
DOI: 10.1111/ppl.12976
|View full text |Cite
|
Sign up to set email alerts
|

Integrative roles of nitric oxide and hydrogen sulfide in melatonin‐induced tolerance of pepper (Capsicum annuum L.) plants to iron deficiency and salt stress alone or in combination

Abstract: There seems to be no report in the literature on the effect of melatonin (MT) in relieving the detrimental effects of combined application of salt stress (SS) and iron deficiency (ID). Therefore, the effect of MT on the accumulation/synthesis of endogenous nitric oxide (NO) and hydrogen sulphide (H2S) and how far these molecules are involved in MT‐improved tolerance to the combined application of ID and SS in pepper (Capsicum annuum L) were tested. Hence, two individual trials were set up. The treatments in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
109
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(131 citation statements)
references
References 160 publications
7
109
0
Order By: Relevance
“…These are the chemical messengers that interrelate with nutrients synergistically or antagonistically and play an imperative role for modulating the physiological responses that lead to salt tolerance (Fatma et al ). Particularly, nitric oxide (NO) has emerged as an ubiquitous important free radical gaseous signaling molecule involved in plant development, various physiological functions and nutrient assimilatory processes and has also been reported to improve plant tolerance to environmental stresses including salt stress, toxic metals, low and high temperature, ultraviolet (UV)‐B, ozone, excess light and various pathogens (Fatma et al , Asgher et al , Per et al , Hasanuzzaman et al , Kaya et al , ). NO plays a pivotal role in alleviating the oxidative damage and improves the antioxidant defense machinery in several salt‐affected plant species (Guo et al , Hasanuzzaman et al , Ahmad et al , , Sehar et al ).…”
Section: Introductionmentioning
confidence: 99%
“…These are the chemical messengers that interrelate with nutrients synergistically or antagonistically and play an imperative role for modulating the physiological responses that lead to salt tolerance (Fatma et al ). Particularly, nitric oxide (NO) has emerged as an ubiquitous important free radical gaseous signaling molecule involved in plant development, various physiological functions and nutrient assimilatory processes and has also been reported to improve plant tolerance to environmental stresses including salt stress, toxic metals, low and high temperature, ultraviolet (UV)‐B, ozone, excess light and various pathogens (Fatma et al , Asgher et al , Per et al , Hasanuzzaman et al , Kaya et al , ). NO plays a pivotal role in alleviating the oxidative damage and improves the antioxidant defense machinery in several salt‐affected plant species (Guo et al , Hasanuzzaman et al , Ahmad et al , , Sehar et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Kushwaha and Singh (2019) and Ahmad et al (2019) have reported various mechanisms through which H 2 S regulates chromium toxicity in crop plants. Regulatory roles of NO and H 2 S were reported for salt and drought stress, as well as iron deficiency in plants (Batista et al 2019, Gohari et al 2019, Jahan et al 2019, Kaya et al 2019a). The role of NO and H 2 S along with that of Si was evaluated for the regulation of cadmium stress in plants (Kaya et al 2019b).…”
mentioning
confidence: 99%
“…In addition, catalase, which is an antioxidant enzyme located in peroxisomes, is targeted by both S ‐nitrosation and persulfidation as well (Begara‐Morales et al ). A recent study also suggests that both NO and H 2 S inhibit catalase activity and complement or antagonize each other in regulating H 2 O 2 content by regulating the antioxidant enzymes (Kaya et al ). Numerous studies have confirmed the functional parallelism of NO and H 2 S regulation in many physiological processes and in hostile environmental conditions such as abiotic and biotic stresses (Janicka et al , Muñoz‐Vargas et al ).…”
Section: Role Of No and H2s As Signaling Moleculesmentioning
confidence: 99%